Le transizioni urbane tra metamorfosi e sostenibilità: Roma: l’assiduo confronto tra formalità e informalità (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2021)
The city of Rome is one of the best examples of how urban space is a scenario of transitions and metamorphosis. This article recognizes the city as an emblem of the dissent between formal and informal, going beyond the definition of Municipality and Metropolitan Area. Cities are potentially a legal system in themselves, capable of producing rules and norms arising from the need for interpretation community requirements. Informality, therefore, can be found in a whole series of behaviors, individual and collective, that move from a logic of solidarity, reciprocity, and gratuitousness. The idea is to show with a case- study how as in the informality emerges the collective interest to produce benefits, social and economic value for the entire community. A new interpretation of the dialogue between formality and informality aspires to be at the center of the debate for a renewed idea of city.